Meta surface-based multiband MIMO antenna for UAV communications at mm-waves and sub-THz bands - Althuwayb, Ayman A.; Saeidi, Tale; Saleh, Sahar; Al Gburi, Ahmed Jamal Abdullah; Timmons, Nick; Karamzadeh, Saeid; Rashid, Nasr; Kaaniche, Khaled; Ahmed Ben, Atitallah; Elhamrawy, Osama I. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Unmanned aerial vehicles (UAVs) need high data rate connectivity, which is achievable through mm-waves and sub-THz bands. The proposed two-port leaky wave MIMO antenna, employing a coplanar proximity technique that combines capacitive and inductive loading, addresses this need. Featuring mesh-like slots and a vertical slot to mitigate open-stopband (OSB) issues, the antenna radiates broadside and bidirectionally. H-shaped slots on a strip enhance port isolation, and a coffee bean metasurface (MTS) boosts radiation efficiency and gain. Simulations and experiments considering various realistic scenarios, each at varying vertical and horizontal distances, show steered beam patterns, circular polarization (CP), and high-gain properties, with a maximum gain of 13.8 dBi, an axial ratio (AR) <2.9, a diversity gain (DG) >9.98 dB, and an envelope correlation coefficient (ECC) <0.003. This design supports drones-to-ground (D2G), drone-to-drone (D2D), and drone-to-satellite (D2S) communications.